2018
DOI: 10.1101/450601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Werner helicase control of human papillomavirus 16 E1-E2 DNA replication is regulated by SIRT1 deacetylation

Abstract: 16Human papillomaviruses (HPV) are double stranded DNA viruses causative in a host of human diseases 17 including several cancers. Following infection two viral proteins, E1 and E2, activate viral replication in 18 association with cellular factors, and stimulate the DNA damage response (DDR) during the replication 19 process. E1-E2 uses homologous replication (HR) to facilitate DNA replication, but an understanding of 20 host factors involved in this process remains incomplete. Previously we demonstrated that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 94 publications
(132 reference statements)
3
22
0
Order By: Relevance
“…HPV16 is responsible for around 50% of HPV-positive cervical cancers and 80 to 90% of HPV-positive oropharyngeal cancers. We have identified several proteins as being involved in E1-E2 DNA replication, including TopBP1, SIRT1, and WRN, all proteins that have key roles in the DNA damage response, HR, and DNA replication ( 25 30 ). Our recent work on WRN demonstrated that deacetylation of this protein by SIRT1 (a protein that also deacetylates TopBP1) promotes binding of WRN to HPV16 origin containing plasmid DNA being replicated by E1-E2 ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…HPV16 is responsible for around 50% of HPV-positive cervical cancers and 80 to 90% of HPV-positive oropharyngeal cancers. We have identified several proteins as being involved in E1-E2 DNA replication, including TopBP1, SIRT1, and WRN, all proteins that have key roles in the DNA damage response, HR, and DNA replication ( 25 30 ). Our recent work on WRN demonstrated that deacetylation of this protein by SIRT1 (a protein that also deacetylates TopBP1) promotes binding of WRN to HPV16 origin containing plasmid DNA being replicated by E1-E2 ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of the CRISPR approach is that wild-type and mutant plasmids can complement the lesion in transient assays. For example, co-transfection of wild-type WRN plasmid in the replication assay in WRN CRISPR edited cells restores wild-type replication phenotypes [ 46 ]. Therefore, enzymatic and structural functions of host factors controlling replication and repair (WRN, for example) can quickly and easily be determined.…”
Section: Resultsmentioning
confidence: 99%
“…The second mechanism that resolves the chicken foot structure and promotes replication restart is homologous recombination (HR), a process that may occur without a DNA DSB from single-stranded DNA (ssDNA) generated at the reversed forks [ 38 ]. HPV replication uses HR, and a host of HR factors interact with HPV genomes [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The paused forks trigger the DDR via increased stretches of ssDNA that activate ATR and the recruitment of the MRE11-RAD50-NBS1 (MRN) complex that mediates HR and activates ATM; HPV-replicating DNA recruits MRN components [ 24 , 40 , 41 , 42 , 48 , 49 , 50 ].…”
Section: Human Papillomavirus Replication and The Dna Damage Respomentioning
confidence: 99%
See 2 more Smart Citations